Impact Of Accessibility And Payment Ease On Pindang Business Growth Through Islamic Microfinance In Muncar - Jannah, Navada Lailyl; Hasanah, Miftahul; Syafi’i, Muhammad (Yayasan Rahmat Islamiyah, 2025)
This study aims to evaluate the influence of accessibility and payment convenience in Islamic microfinance on the growth of pindang businesses in Muncar, Banyuwangi. Pindang businesses represent a vital sector within Muncar's fisheries industry but often face challenges due to limited capital. Islamic microfinance offers an alternative financing model aligned with Sharia principles and is expected to foster the growth of pindang businesses through improved accessibility and ease of payment. A quantitative approach was employed using an inferential associative method, with the research conducted among pindang entrepreneurs in Muncar, Banyuwangi. A total of 35 respondents participated in the study. Data were collected through questionnaires, and the analysis methods included validity tests, reliability tests, classical assumption testing, multiple linear regression analysis, partial tests (T-test), simultaneous tests (F-test), and the coefficient of determination (R²). The results indicate that accessibility and payment convenience have a positive and significant impact on the growth of pindang businesses through Islamic microfinance products. These two variables contribute 95.3% to the growth of pindang businesses, while the remaining 4.7% is influenced by other factors not examined in this study. Therefore, Islamic microfinance can serve as an effective new solution to support the development of pindang businesses in Muncar.